The Consumption Paradigm in Marketing - Eka Ardianto (Gadjah Mada International Journal of Business, 2003)
This article elaborates consumption paradigm in marketing. In background, this paper reviews different perspectives of consumption: economic perspective and marketing perspective. In ontology, this work describes various issues regarding consumption view. In epistemology, this article demonstrates how marketers especially researches explore the consumption phenomena. In methodology, the article describes experiential marketing –one of applied consumption paradigm in marketing, which could be an alternative choice of marketing practices.